Excessive dietary supplement use and blood pressure among Brazilian male resistance training practitioners and bodybuilders. (2nd November 2019) - Gomes Gonçalves e Silva, Daniela Conceição; Bavaresco Gambassi, Bruno; Dantas, Milla Gabriela Belarmino; Lima-Oliveira, Jhonatan; Vieira de Carvalho, Sílvia Lorena; Morais, Priscilla Alencar de Oliveira; Sá, Camila Almeida; Cotrim, Helma Pinchemel; Santos, Azenildo Moura; Sobral Filho, Dário Celestino; Schwingel, Paulo Adriano
ABSTRACT: Objective: The aims of the present research were to determine the prevalence of the use of dietary supplements and anabolic-androgenic steroids (AAS) without professional guidance in the countryside of Northeastern Brazil, and to compare blood pressure (BP) between nonusers of dietary supplements, thermogenic supplement users and AAS users. Methods: The sample consisted of 346 resistance training (RT) practitioners and bodybuilders. The participants answered a questionnaire on the use of dietary supplements and/or AAS. In addition, the participants underwent BP assessment. Results: 76.9% of the sample consumed dietary supplements and AAS at some point in their lives. 66.8% (95%CI: 61.5–71.7) of our sample used only food supplements without any guidance from a qualified professional. AAS and cosmetic doping was reported by 8.1% (95%CI: 5.6–11.2%) and 2.0% (95%CI: 1.0–4.2%) of the sample, respectively. Regarding BP, a significant difference was observed for systolic BP when nonusers of dietary supplements were compared to users of thermogenic supplements (126.5 ± 15.1 mmHg s . 134.7 ± 14.5 mmHg; p = .034) and when compared to AAS users (126.5 ± 15.1 mmHg vs . 136.6 ± 12.2 mmHg; p = .010). Conclusions: Our findings point to excessive consumption of dietary supplements and AAS (without professional guidance) by RT practitioners and bodybuilders. In addition, we observed high systolic blood pressure in users of thermogenic supplements and AAS users.